Моделирование зависимости электрического сопротивления гранулированных токопроводящих сред от протекающего в них импульсного тока - Захарченко, С.Н. (Технічна електродинаміка, 2012)
Results of research of dependence of equivalent electric resistance of a layer of metal granules from time and from a current proceeding in a layer on example Al are given. Characteristics of areas of dependence of resistance from time are described. The critical analysis of the functions approximating nonlinear dependence of resistance from a current by means of three known and one original criteria is carried out. It is shown that in the best way given dependence is described by hyperbolic function of the first degree on which basis the equivalent circuit of electric resistance of the granulated current-carrying medium is offered.